Konsep Analisis SWOT dalam Meningkatkan Kualitas Pelayanan dan Kepuasan Orangtua Lembaga TK Swasta RK Bintang Timur Pamatang Raya - Saragih, Normalina; Sherly, Sherly; Herman, Herman (Attractive : Innovative Education Journal, 2024)
Quality education is the hope and demand of every parent or community as customers of educational institutions. A quality educational institution is an educational institution that is able to satisfy parents or the community and is able to attract their hearts with the various strategies implemented by the institution. The higher the quality of service provided by an educational institution, the more interested the educational institution will be. The development of education in the city of Simalungun district, namely Pamatang Raya, is currently quite rapid, especially at the Early Childhood Education (PAUD) level. This is marked by the presence of PAUD Educational Institutions which have been established in neighboring sub-districts and sub-districts and are even close to one another and similar educational institutions which are accessible to the community both in terms of location/location and in terms of financing. And at times like this, every institution tries to improve the quality of its services to attract the interest of parents or the surrounding community and increase the satisfaction of students' parents with the services provided by the institution. In order to improve the quality of service and the satisfaction of parents, the East Star Private Kindergarten Education Institution must work together to find the right strategy so that this institution becomes increasingly popular with the public. One strategy that this Institute considers very appropriate is SWOT analysis. Through this analysis, the RK Bintang Timur Pamatang Raya Private Kindergarten Education Institution can find out the strengths, weaknesses, opportunities and challenges that need to be considered in order to improve service quality and parent satisfaction. Keywords: Improving Service Quality, Quality of Parental Satisfaction